Curriculum Theorycide! Calling for an Itinerant Curriculum Theory - Paraskeva, João (Nastava i vaspitanje, 2025)
The curriculum field faces a ‘theorycide’, which is not necessarily the absence of a theory, but the yoke of a ‘non-theory theory’ momentum which has worsened, especially in the last half of the last century. Drawing on a critical, anticolonial, and decolonial theoretical framework, my aim in this essay is to examine the hegemonic and counter-hegemonic Eurocentric debates in our field, but within the context of modernity and its eugenic coloniality, the Prosperous reason, thus framing the epistemicidal nature of the field. In so doing, the essay dissects the contemporary theoretical hemorrhage we face as a field, what I have called ‘curriculum involution’ and ‘curriculum imparity.’ A lethal theoretical void has emerged from the epistemological civil war within and between dominant and counter-dominant traditions, triggering what I call the theorycide. The article advocates a way out of such ‘involution’ through an itinerant curriculum theory, a non-derivative anti-colonial and de-colonial approach responsive to the world’s epistemological difference, and diversity. The essay frames ICT as a declaration of epistemological independence against the scientific monumentalism of Eurocentrism that egregiously dehumanizes the legitimacy of Caliban’s reason.